Dynamic intraoperative MRI in transsphenoidal resection of pituitary macroadenomas: A quantitative analysis. Issue 3 (23rd September 2013) - Boellis, Alessandro; Espagnet, Maria Camilla Rossi; Romano, Andrea; Trillò, Giuseppe; Raco, Antonino; Moraschi, Marta; Bozzao, Alessandro
<x xml:space="preserve">Abstract</x> Purpose To compare intraoperative dynamic contrast‐enhanced (dCE) sequences with conventional CE (cCE) in the evaluation of the surgical bed after transsphenoidal removal of pituitary macroadenomas. Materials and Methods Twenty‐one patients with macroadenoma were selected. They all underwent intraoperative magnetic resonance imaging (iMRI) (1.5T) acquisitions during transsphenoidal resection of the tumor. For each patient, dCE and cCE images were acquired in the operating room after tumor removal. The mean values of surgical cavities volumes were measured and statistically compared through Student's t‐test analysis. Informed consent to iMRI was obtained from the patients as a part of the surgical procedure. Institutional Review Board (IRB) approval was obtained. Results No patient showed recurrence within at least 1 year of follow‐up. Two patients showed residual tumor in the iMRI. Intraoperative analysis of the remaining 19 demonstrated that the mean value of the surgical cavities was significantly bigger in dCE than in cCE images (2955 mm3 vs. 1963 mm3, respectively, P = 0.022). Conclusion This study demonstrated underestimation of surgical cavity by conventional iMRI, simulating residual tumor and potentially leading to unnecessary surgical revision. J. Magn. Reson. Imaging 2014;40:668–673. © 2013 Wiley Periodicals, Inc.